2015
DOI: 10.1371/journal.pone.0118212
|View full text |Cite|
|
Sign up to set email alerts
|

First Clinical Experience of Intra-Operative High Intensity Focused Ultrasound in Patients with Colorectal Liver Metastases: A Phase I-IIa Study

Abstract: BackgroundSurgery is the only curative treatment in patients with colorectal liver metastases (CLM), but only 10–20% of patients are eligible. High Intensity Focused Ultrasound (HIFU) technology is of proven value in several indications, notably prostate cancer. Its intra-operative use in patients with CLM has not previously been studied. Preclinical work suggested the safety and feasibility of a new HIFU device capable of ablating volumes of up to 2cm x 2cm in a few seconds.MethodsWe conducted a prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…For this preclinical work, temperatures of the skin and amniotic cavity were verified using thermocouples. Guidance by ultrasound is sufficient to target accurately the region to be treated and evaluate the resulting coagulation. Temperature estimation during treatment will not be used clinically; it is not an absolute requirement if targeting is accurate.…”
Section: Discussionmentioning
confidence: 99%
“…For this preclinical work, temperatures of the skin and amniotic cavity were verified using thermocouples. Guidance by ultrasound is sufficient to target accurately the region to be treated and evaluate the resulting coagulation. Temperature estimation during treatment will not be used clinically; it is not an absolute requirement if targeting is accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The principal interest lies in the possibility of treating hepatic parenchyma in a short period of time (ablation of 5–7 cm 3 in 40 s) without any organ puncture or blood contact. The intraoperative approach selected for the toroidal HIFU treatment (after surgical laparotomy) makes it possible to reach all regions of the liver without penetrating the hepatic capsule, particularly in Human for whom all liver sectors are accessible by this strategy [ 65 ]. This configuration also enables the protection of surrounding organs and eliminates the risk of secondary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides allowing a better staging of malignancies, large areas of liver can be rapidly ablated in an open procedure. In a feasibility study by Dupré et al [60] , this approach was found to be effective in patients with colorectal liver metastases. In 30 ablations performed in 15 patients, intra-operative HIFU was found to be safe, feasible, and without damage to neighboring tissues [60] .…”
Section: Figure 2 Axial Computed Tomography Images Before and After Rmentioning
confidence: 99%
“…In a feasibility study by Dupré et al [60] , this approach was found to be effective in patients with colorectal liver metastases. In 30 ablations performed in 15 patients, intra-operative HIFU was found to be safe, feasible, and without damage to neighboring tissues [60] . Recently, Gandini evaluated in an animal model the use of HIFU for assisting liver resection in an open procedure [61] .…”
Section: Figure 2 Axial Computed Tomography Images Before and After Rmentioning
confidence: 99%